PENGARUH JENIS DAN KONSENTRASI ZAT PENGATUR TUMBUH ORGANIK TERHADAP PERTUMBUHAN STEK LADA (Piper nigrum L.) - Yuliatul Muslimah; Iwandikasyah Putra; Ledy Diana (Jurnal Agrotek Lestari, 2018)
This research to know influence of some and concentration hormonal growth organic to the growth cutting of peppercorn real and whet her there is  interaction both of factor.  This research have been executed by in Garden Agriculture Faculity of Teuku  Umar University Meulaboh,  Aceh Barat  Started 14 August up to 27 October 2015. This research to used is a randomized  blokc desigh (RBD) with  3 x 4 and  3 with  there replications. The first factor consist of some hormonal growth organic of 3 level extract Shallot, young coconut water, and extract bean sprouts. Second factor consisting of 4 level that is concentration of some hormonal growth organic of  0% (contro), 15 %, 25% and 35%. The result showed that the influence of some organic hormonal growth were affected to amount of shoot, long of shoot, root, and root wight. This research show that the concentration some hormonal growth affeected to amount of shoot, long of shoot, root, long of root and root wight. There was interaction between influence of some and concentration hormonal growth organic on all parameters of observation. Keywords: concentration, kind of amelioran, organic hormonal growth, pepper cuttings